Critical review of the analysis of brominated flame retardants and their environmental levels in Africa. (December 2016) - Brits, Martin; de Vos, Jayne; Weiss, Jana M.; Rohwer, Egmont R.; de Boer, Jacob
Abstract: World-wide, the prevalence of brominated flame retardants (BFRs) is well documented for routine analysis of environmental and biological matrices. There is, however, limited information on these compounds in the African environment and insufficient information on the analytical approaches used to obtain data. This paper presents a review on BFR levels in the African environment and the various analytical methodologies specifically applied in Africa for polybrominated diphenyl ethers (PBDEs), polybrominated biphenyls and alternative-BFRs. The analyses include liquid sample preparation using liquid-liquid and solid phase extraction and solid sample preparation involving Soxhlet extraction, with ultrasound-assisted extraction increasingly being applied. Instrumental detection techniques were limited to gas chromatography coupled with electron capture detector and electron impact ionisation with single quadrupole mass spectrometers. Information on congener profile prevalence in indoor dust, soil, aquatic environment (water, sediment, and aquatic organisms), eggs, wastewater treatment plant compartments, landfills (leachate and sediment) and breast milk are presented. Although PBDEs were inconsistently detected, contamination was reported for all investigated matrices in the African environment. The manifestation in remote regions indicates the ubiquitous prevalence and long-range transport of these compounds. Levels in sediment, and breast milk from some African countries were higher than reported for Asia and Europe. Due to limited data or non-detection of alternative-BFRs, it is unclear whether banned formulations were replaced in Africa. Most of the data reported for BFR levels in Africa were obtained in non-African laboratories or in South Africa and formed the basis for our discussion of reported contamination levels and related methodologies. Highlights: Current analytical techniques for BFR analysis in Africa were reviewed. BFR levels in the African environment were also reviewed. BFRs were ubiquitously present in the African environment. There was limited data on alt-BFRs as replacements for banned formulation in Africa.